Status of flood vulnerability area in an ungauged basin, southwest Nigeria - Sobowale, A.; Oyedepo, J. A. (International Journal of Agricultural and Biological Engineering, 2013)
Many rivers in Nigeria had been ungauged in the last three decades; this worrisome scenario has impacted negatively on the livelihood of people who live in flood plains. The general lack of up to date streamflow data has made river basin management problematic especially in the area of flood risk management and the development of a real time flood warning system. Flood studies were carried out in the Ogun River Basin in the southwest Nigeria using synthetic data generated by Rainfall-Runoff Modeling using a combination of the Natural Resources Conservation Service (NRCS) curve number model and digital terrain modeling using ArcGIS® 9.3 software to identify vulnerable areas in relation to synthesized flood waves generated from the basin, extent of inundation and ranking of the flash points that was equally done using proximity to hazard source as a criteria. The total area in the basin covered by fresh water swamps, salt marsh, and tidal flats at the lower course of Ogun river is 49 km2, while the spatial extent of the entire wetland is 556 km2 accordingly. When a peak flood volume of 4 270 million m3 generated in September is routed into the fresh water swamp, about 33.4 m of flood depth was left unaccommodated, which will cause inundation of the entire flood plain and severe damage on its path. Over 1.4 million inhabitants were identified to be at risk in the area. When the entire wetland was considered, the flood wave was reduced to an average depth of 8.5 m which is still capable of causing grave damages in the remaining parts of the flood plain. The flood wave was found to have a residence time of about 45 days. Appropriate recommendations were given for practical adaptations.